Assessment of Quantity Surveying Firms' Process and Product Innovation Drive in Nigeria - Onyeagam Onyealilam Peter; Emmanuel Chidiebere Eze; Adegboyega Adesoji Anthony (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose- Innovation repositions and strengthens the competitive advantage and revenue drive of corporate businesses. The aim of this study is to assess the extent of the process and product innovation in Nigerian Quantity Surveying firms with a view to determining the innovative tools/concepts used. Design/Methodology- The study adopted a questionnaire survey in which simple random sampling was used to collect data from Quantity Surveyors working with Quantity Surveying firms in the study area. Relative importance Index, mean score, frequencies, andpercentages were used to analyze the data collected, and Rogers' innovation adopters categorization was employed to determine the level of adoption of innovation by Quantity Surveyors. Findings- The study found that Quantity Surveying firms do not engage the services of innovation specialist because of financial constraint. The most adopted innovative tools/concept by Quantity Surveying firms are MS Excel, Computer Aided Taking-off, CATO, and CA Estimating, and these firms are an early majority in the adoption of process and product/technological innovations. Practical Implications- The study would assist Quantity Surveying firms who have notembraced innovation to do so, by adopting and incorporating innovative practices in the running of the business transactions and operations to improve clients' satisfaction, profit generation, andcompany image.